Outpatient experiences with the mobile JKN queuing system: Patient satisfaction at a hospital in Makassar - Musyawir, Andi Khairul; Maturbongs, Cesilia Indriayu (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Recent advancements in healthcare technology have introduced innovations such as the Mobile JKN queuing system, designed to streamline outpatient registration and enhance patient convenience. However, there remains a gap in understanding patient experiences and satisfaction with these digital interventions in rural hospital settings. This study aimed to explore and describe outpatient experiences using the Mobile JKN queuing system and assess satisfaction levels at Stella Maris Hospital in Makassar. A qualitative phenomenological approach was employed, involving in-depth interviews, observation, and documentation with outpatients, BPJS officers, and outpatient department leaders. Findings revealed diverse patient experiences, with some respondents expressing appreciation for reduced on-site waiting times, while others were dissatisfied due to extended waiting despite app registration. Additional factors influencing satisfaction included lack of social interaction, inaccurate information, inconsistent scheduling, and limited doctor availability. Relational, functional, and service integration issues contributed to negative perceptions and identified existing gaps in the digital queuing system. These insights underscore the need for ongoing evaluation and targeted improvements in digital health service delivery in rural areas, with implications for optimizing patient-centered care and technology adoption.